Crop production potential of rural areas within the European Communities. 3. Soils, Climate and Administrative Regions - Reinds, G.J.; de Koning, G.H.J. (WRR, 1992)
Economics; European Union
Keywords: Cation-Exchange Capacity; Economics; Economie; European Union; Europese Unie